Focus Group Interview: Data Collection - Saloma, Pawi; Zabidah, Putit; Jane, Buncuan (Malaysian Nurses Association, 2011)
Adjunct to our previous article Challenges in conducting Focus Group: Moderators’ experiences, authors thought it would be fair to further discuss about the procedures/steps in data collection during focus group interview. These include the interview guide, composition of the group, number of focus group, sample size, role of moderator and recording the data.